2009
DOI: 10.1002/cmdc.200800259
|View full text |Cite
|
Sign up to set email alerts
|

How to Extend the Use of Grid‐Based Interaction Energy Maps from Chemistry to Biotopics

Abstract: Many computational tools routinely used in chemistry could successfully be applied to the biosciences since protein-protein and protein-ligand interactions are governed by the laws of chemistry. This paper shows that it is possible to extend the use of existing computational tools from their traditional application field (e.g. chemistry) to culturally-related research areas by the implementation of simple but well-designed utilities. In particular, a computational strategy obtained by combining GRID (the progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In particular, according to Pastor et al (23), we assumed that the presence of any water molecule in its observed crystallographic position was energetically favorable. In practice, we used GRID to calculate the MIFs for the water probe and BIOCUBE4mf (24) to select the regions satisfying energetic criteria (energy threshold). Results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, according to Pastor et al (23), we assumed that the presence of any water molecule in its observed crystallographic position was energetically favorable. In practice, we used GRID to calculate the MIFs for the water probe and BIOCUBE4mf (24) to select the regions satisfying energetic criteria (energy threshold). Results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While negative energy levels of the contours describe regions at which ligand binding should be favored, positive energy levels normally characterize the shape of the target. Some of the recent applications of the GRID method include determining energetically favorable binding sites and characterization of their surface properties [51], building predictive pharmacophore models [52], classification and comparison of ligand-binding sites [53], and rational design of potent inhibitors of influenza virus sialidase [54]. Many times GRID maps are also used as input descriptors in CoMFA, GOLPE or SIMCA for QSAR or 3D-QSAR analyses [55].…”
Section: Gridmentioning
confidence: 99%
“…BICUBE [37] was used to extract isosurfaces from molecular interaction fields, obtained by GRID hydrophobic (DRY), hydrogen bond donor/hydrogen bond acceptor (OH2), and H probes. The last probe is used to characterize molecular shape, while DRY and OH2 probes are chosen to characterize hydrophobic and polar part of molecules, respectively.…”
Section: Modelingmentioning
confidence: 99%